SYNBIOTICS SUPPLEMENTATION AMELIORATES HIGH FAT AND SUGAR DIET-ASSOCIATED OXIDATIVE STRESS AND HISTOLOGICAL ARCHITECTURE OF INTESTINE, LIVER AND KIDNEY IN RATS - H. Rashid; S. M. Ishtiaq; Z. Hussain; M. N. Faisal; H. Anwar; A. S. Qureshi; M. ur Rasheed; M. Rasheed; A. Riaz; J. A. Khan (Journal of Animal and Plant Sciences, 2022)
The present study is designed to investigate therapeutic strategies to favorably change the intestinal microbiota through ‘bacteriotherapy’ involving the use of synbiotics, a combination of probiotics (Lactobacilli spp, Bifidobacteria spp. and Streptococcus spp.) and prebiotics (Dandelion and Glycyrrhizin) in high fat and high sugar (HFHS) diet-associated liver disease. The involvement of hepatic portal system with kidneys to modulate gut microbiota with synbiotics supplements is the novel strategy of the present study. The four diet treatment groups were the vehicle control (Veh), diet supplemented with synbiotics (Syn; probiotics; 2 x 106 CFU/rat/day + prebiotics; 300 mg/kg feed); HFHS diet group (36 + 40 %) and HFHS+Syn group. All the treatments were arranged in a completely randomized design. Synbiotics and HFHS were provided throughout the 14-week experimental period. The results showed that synbiotics supplementation significantly lowered serum cholesterol, triglyceride, aspartate aminotransferase, alkaline phosphatase, bilirubin, creatinine, uric acid, total protein, total oxidant status and malondialdehyde as compared to the HFHS+Veh group. Moreover, a significant increase in high-density lipoprotein and anti-oxidant parameters such as total anti-oxidant capacity, paraoxonase and arylesterase showed the ameliorative potential of synbiotics in the HFHS+Syn group. The histological images of the intestine, liver and kidneys in the HFHS+Veh group showed fat accumulation and cytoplasmic vacuolation whereas, synbiotics significantly improved histological architecture in the HFHS+Syn group. It was concluded that diet supplementation with synbiotics might be a potential candidate for prevention or adjuvant treatment of metabolic diseases involving oxidative stress.
Keywords: Synbiotics; Nonalcoholic fatty liver disease; Oxidative stress; Gut-Liver axis